The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s2175-78602011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Manganese accumulation and its effects on three tropical aquatic macrophytes: Azolla caroliniana, Salvinia mínima and Spirodela polyrhiza

Abstract: The phytoremediation technique, which consists of using plants to remove ions, has been increasingly chosen over past decades due to its low-cost technology to mitigate contaminated areas. The aim of this study was to evaluate the potential of the aquatic macrophytes, Azolla caroliniana Willd, Salvinia minima Baker and Spirodela polyrhiza (L.) Schleiden, to accumulate manganese (Mn), an element which, at high concentrations, may be toxic to human populations. The three species accumulated Mn in their tissues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(40 reference statements)
0
4
0
3
Order By: Relevance
“…However, excess Mn can cause iron and magnesium deficiency due to its entry into porpyrin in the place of iron and magnesium (Sideris and Young, 1949). Reductions of photosynthetic pigments by excess Mn exposure were reported in both terrestrial plants, such as Pisum sativum (Rezai & Farboodina, 2008;Gangwar et al, 2010), H. vulgare (Demirevska-Kepova et al, 2004), Glycine max (Wu, 1994) and Phaseolus vulgaris (Gonzalez et al, 1998) and aquatic plants, such as A. caroliniana, S. minima and S. polyrhiza (Lizieri et al, 2011). Similar to Mn, Ni also caused an increase in the pigment amount at low levels.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 92%
“…However, excess Mn can cause iron and magnesium deficiency due to its entry into porpyrin in the place of iron and magnesium (Sideris and Young, 1949). Reductions of photosynthetic pigments by excess Mn exposure were reported in both terrestrial plants, such as Pisum sativum (Rezai & Farboodina, 2008;Gangwar et al, 2010), H. vulgare (Demirevska-Kepova et al, 2004), Glycine max (Wu, 1994) and Phaseolus vulgaris (Gonzalez et al, 1998) and aquatic plants, such as A. caroliniana, S. minima and S. polyrhiza (Lizieri et al, 2011). Similar to Mn, Ni also caused an increase in the pigment amount at low levels.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 92%
“…In general, the deleterious direct effects of TEs include the disturbances in gaseous exchange, respiration, and CO 2 fixation [3,20]. It was found that an excess amount of TEs on the photosynthetic apparatus is manifested in the degradation of enzymes involved in chlorophyll biosynthesis, decreased chlorophyll and carotenoid contents, changes within reaction center, photosystem II and photosynthetic rate, as well as disturbances in the transport of electrons between the antenna system and photosystems [50,53,58,59,60,61,62,63,64]. Furthermore, the elevated concentration of TEs may lead to the inactivation of key enzymes of various metabolic pathways, as well as blocking the functional groups of metabolically important molecules.…”
Section: Harmful Effects Of Tes and Their Consequence On Plant Orgmentioning
confidence: 99%
“…Fonte: Autores A redução da biomassa das plantas de S. polyrhiza, em ambos experimentos, pode ter sido ocasionada pelo desequilíbrio nutricional causado pelo excesso do Fe e Mn na solução, adicionado ao decréscimo do conteúdo de clorofila verificado nessas plantas. Lizieri, et. al.…”
Section: Efeitos Do Fe Sobre a Produção De Biomassa Das Plantas De Riunclassified
“…Não foram observadas alterações significativas no conteúdo de clorofila para plantas de R. natans submetidas ao estresse por Fe, entretanto, plantas expostas à concentração de 18 mg/L de Fe mostraram uma tendência para aumento deste pigmento (Figura 9), sendo este resultado também observado para a produção da biomassa. Diversos estudos têm demonstrado que o excesso de Mn reduz o conteúdo de clorofila (Clairmont et al, 1986;Teixeira et al, 2004, Lizieri et al, 2011. Pell et al (1994) afirmam que toda mudança no ambiente que provoque um estresse sobre as plantas acaba provocando danos no processo fotossintético, dentre eles, a ocorrência de danos envolvendo os movimentos estomáticos, a coleta de luz e a etapa bioquímica de fixação do CO2.…”
Section: Efeitos Do Mn E Do Fe Sobre O Conteúdo De Clorofila Totalunclassified
See 1 more Smart Citation